Virtual Reality and Fear of Shark Attack: A Case Study for the Treatment of Squalophobia. (October 2020) - Malbos, Eric; Burgess, George H.; Lançon, Christophe
Research treatment protocols are rare regarding an unusual anxiety disorder, namely the fear of sharks (squalophobia). As a possible solution, the effectiveness of virtual reality (VR) exposure therapy for this phobia was tested. The advantage of using VR becomes clearer when a real life set up is impractical, such as exposing a phobic patient to a feared large marine organism, the shark. The effects were evaluated in a single case study involving multiple context-graded aquatic virtual environments with a virtual shark and using affordable VR apparatus and software. Assessment was based on self-report questionnaires. Scores the psychometric instruments exhibited a discernable reduction in fear toward sharks. Such gains were maintained at a 12-month follow-up. Presence rates indicated immersion when confronted to a three-dimensional (3D) virtual shark. This initial study revealed the potential of VR for the treatment of marine biota phobia and its potential to recreate diverse situations for exposure therapy.